2013
DOI: 10.1292/jvms.13-0104
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Dobutamine and Phenylephrine Infusion in Sevoflurane-anesthetized Thoroughbred Horses

Abstract: To determine dose-dependent cardiovascular effects of dobutamine and phenylephrine during anesthesia in horses, increasing doses of dobutamine and phenylephrine were infused to 6 healthy Thoroughbred horses. Anesthesia was induced with xylazine, guaifenesin and thiopental and maintained with sevoflurane at 2.8% of end-tidal concentration in all horses. The horses were positioned in right lateral recumbency and infused 3 increasing doses of dobutamine (0.5, 1.0 and 2.0 µg/kg/min) for 15 min each dose. Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
4
9
1
1
Order By: Relevance
“…Heart rate was reduced, most likely as a reflex response to the increased afterload. The concurrent drop in CO and SV is consistent with previous reports on cardiovascular effects of phenylephrine in horses using similar dose ranges to this study [9,10]. The decrease in local microvascular perfusion at all three measurement sites with phenylephrine indicates a redistribution of blood away from the intestinal measurement site due to the a-mediated vasoconstriction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Heart rate was reduced, most likely as a reflex response to the increased afterload. The concurrent drop in CO and SV is consistent with previous reports on cardiovascular effects of phenylephrine in horses using similar dose ranges to this study [9,10]. The decrease in local microvascular perfusion at all three measurement sites with phenylephrine indicates a redistribution of blood away from the intestinal measurement site due to the a-mediated vasoconstriction.…”
Section: Discussionsupporting
confidence: 91%
“…The peripheral vasodilation, indicated by a decrease in SVR, combined with an increase in CO and SV positively influenced local blood flow in this experiment. Previous studies in anaesthetised horses , cats and man using comparable doses, showed similar results regarding systemic haemodynamic parameters. In terms of altering local mesenterial blood flow or oxygen delivery, previous studies in hypotensive foals or experimental models of sepsis failed to show a significant influence on the gastrointestinal perfusion, although jejunal mucosal blood flow has been shown to improve after cardiac surgery with dobutamine infused at 2.7 ± 0.1 μg/kg bwt/min .…”
Section: Discussionsupporting
confidence: 72%
“…DAP, diastolic arterial blood pressure; MAP, mean arterial blood pressure; SAP, systolic arterial blood pressure right-ventricular dP/dtmax indicating a positive inotropic effect. In contrast, most of the studies in anaesthetized horses showed an increase in SV and or Qt as the main mechanism of dobutamine improving systemic blood pressure (Craig et al, 2007;Dancker et al, 2018;Lee et al, 1998;Ohta et al, 2013;Schauvliege et al, 2008;Swanson et al, 1985;de Vries et al, 2009). These contradictory results could be attributed to the administration of inhalation anaesthetics causing vasodilation and consequently favouring a larger SV.…”
Section: Discussionmentioning
confidence: 98%
“…Hinchcliff et al (1991) reported an increase in systemic blood pressure without detectable changes in Qt and SV using a considerably lower dose of dobutamine (0.5 µg kg −1 min −1 ) in conscious horses. Conversely, in anaesthetized horses, dobutamine seems to increase systemic blood pressure primarily by improving Qt and SV (Craig, Haskins, & Hildebrand, 2007;Dancker et al, 2018;Lee, Clarke, Alibhai, & Song, 1998;Ohta et al, 2013;Schauvliege et al, 2008;Swanson, Muir, Bednarski, Skarda, & Hubbell, 1985;de Vries, Brearley, & Taylor, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation